PERANAN PERUSAHAAN PENJAMINAN DALAM MENGATASIPERMASALAHAN UMKM MENGAKSES KREDIT DI SEKTOR PERBANKAN(SETELAH BERLAKUNYA UNDANG-UNDANG NOMOR 1 TAHUN 2016 TENTANG PENJAMINAN) - Saraswati, Luh Putu Prema Shanti Putri (Jurnal Hukum & Pembangunan, 2021)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the development of the Indonesian economy.So far, MSMEs are still faced with various kinds of obstacles,one of which is that MSMEs still face problems related to limited access to funding to financial institutions.Limited access to funding to financial institutions is partly due to the limited assets owned by MSMEs to be used as collateral for bank loans.Guarantee is theactivity of providing guarantees by the Guarantor for the fulfillment of Guaranteed financialobligations to the Recipient of the Guarantee.Guarantee Company is a legal entity engaged in finance with the main business activity of conducting guarantees. The problem examined is how the role of the guarantee company in helping MSMEs access credit in the banking sector and how the guarantee mechanism is carried out by the credit guarantee company. This study uses normative juridical researchmethods.